The Role of Ancient Medicine in Modern Medicine - Naimov Dilshod Qayim o’g’li (Journal of Science in Medicine and Life, 2023)
The article is devoted to studying the relevance alternative medicine in the modern world. The history of development is described this method of treatment, statistics on the use of various methods of traditional medicine in the 21st century. A feature of this study is the use of a survey in the form of anonymous questioning of people different ages and types of employment.